The Analysis on the Key Factors of Fire Rescue Course Content Design A Case Study of Miaoli County - Chang, Hung-Teng; Lo, Chih-Yao; Tu, Wen-Chia kevin (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
This study discussed the factors affecting the design of the fire rescue and training courses for firefighters in Miaoli County. A questionnaire survey was conducted on firefighters. The content of the fire rescue courses held by Miaoli County Fire Bureau was discussed. Based on literature review and expert opinions upon Delphi method, this study analyzed the indicators of influencing factors. A hierarchical architecture was established. The weights affecting the design factor indicators affecting the fire rescue courses were obtained with the survey and analytic hierarchy process, and then were summarized and analyzed to establish a weight system.